Automated structuring of company profiles - Ljubič, Peter (Metodološki zvezki, 2006)
Selection of partners with appropriate competencies, resources and skills is one of the crucial tasks in the creation of virtual organizations. Partner selection can be facilitated by structuring competencies in an ontology which provides a shared conceptualization. Manual ontology construction is a time and resource consuming activity. Alternatively, there are text mining, conceptual clustering and visualization tools available that can be used for semi-automated ontology creation. This paper proposes a methodology and presents tools which facilitate competency structuring from unstructured company data. These tools have been applied to the reconstruction of the Yahoo! business ontology.
Keywords: poslovanje podjetja; računalniški sistemi; informacijske storitve; umetna inteligenca; ontologija; ontology